The role of venture capital in the creation of public companies - Barry, Christopher B.; Muscarella, Chris J.; Peavy, John W.; Vetsuypens, Michael R. (Journal of Financial Economics, 1990)
We examine an exhaustive set of initial public offerings (IPOs) by venture-capital-backed companies between 1978 and 1987. We find that venture capitalists specialize their investments in firms to provide intensive monitoring services. Consistent with their monitoring role, the venture capitalists take concentrated equity positions, maintain their investment beyond the IPO, and serve on the boards of their portfolio firms. The quality of their monitoring services appears to be recognized by capital markets through lower underpricing for IPOs with better monitors.